Unpacking the Implementation of Problem Based Learning in Teaching Writing Procedure Text toward Secondary Students - Hamimah Zahra; Yogi Setia Samsi (Journal of English Language Learning, 2022)
Writing ability is very important for every student in learning English. Many students have difficulty in the writing process. Based on the 2013 curriculum, which emphasizes collaborative and student-oriented learning where students can develop their thinking and knowledge skills by themselves. Based on the 2013 curriculum, there are four recommended learning models to be applied in learning English, one of which is Problem Based Learning. Problem based learning is the right model to solve students' problems in writing, especially in writing procedure text. This research is a qualitative research with a descriptive case study research design. This study aims to investigate the implementation of Problem Based Learning in teaching writing procedure text and to investigate students' responses to teaching writing procedure text through Problem Based Learning. In this study, the subjects used were 21 twelfth graders. This study uses observation and interviews in data collection and research instruments. This study conducted observations for two meetings and conducted interviews with four students. Data were analyzed using thematic analysis. The result of this research is that the teacher implements Problem Based Learning in accordance with the existing stages. Another result is that students have a positive response to the implementation of Problem Based Learning, including Problem Based Learning (PBL) makes students feel comfortable, not bored, and having difficulties, Problem Based Learning (PBL) makes students more active, Problem Based Learning helps in developing students' thinking skills, and Problem Based Learning (PBL) helps students to write procedure text. Problem Based Learning model can be implemented in teaching writing procedure text. Problem-Based Learning as a learning model, able to motivate students to contribute to the learning process in class and able to invite students' interest in writing.